The Role of Mobile Banking in Pakistan with Regard to Financial Inclusion - Ali, Mehak; Alamgir, Muhammad; Rehmani, Umar Hayat (Annals of Human and Social Sciences, 2024)
The main purpose of this study is to determine the role of mobile banking and its effects on economic growth and financial inclusion in Pakistan when gender acts as a moderating variable. As we know, mobile banking services remove time and space barriers from banking tasks like checking account balances and transferring funds between accounts, saving customers' time when visiting banks to use various banking services. Data was collected from the secondary source website of ‘State Bank of Pakistan’ as well as from various journals and articles spanning ten years, i.e., 2011–2021. Also, various analyses were applied to the secondary data, i.e., the unit root test, multicollinearity, descriptive statistics, and Ordinary Least Square (OLS) regression analysis by using E-views 7.0, and it was concluded that mobile banking was among the significant determinants of financial inclusion and economic growth (GDP). Whereas, in moderator gender male behavior effects significantly among mobile banking variables, i.e., Access to Mobile Phone & financial inclusion variables, i.e., (Number of mobile banking accounts & Savings) and the G.D.P. And female behavior seemed to act as a key moderating factor among both the mobile banking & financial inclusion determining factors, i.e., Number of mobile banking accounts. However, it has insignificant effects between the mobile banking variable, i.e., Access to Mobile Phone and financial inclusion variable, i.e., savings. Moreover, to improve generalizability, future research on other countries could be undertaken in addition to this one, using a larger data set because this study was limited to Pakistan only.